Interannual variability of estimated monthly nitrogen deposition to coastal waters due to variations of atmospheric variables model input - Pineda Rojas, Andrea Laura (2010)
In this work, the influence of the interannual variation of meteorological input data on the nitrogen (N) deposition estimated applying atmospheric dispersion models is discussed. As a case study, the deposition of atmospheric oxidized N coming from the NOx generated in the Metropolitan Area of Buenos Aires to waters of de la Plata River is evaluated for three years, considering high spatial (1 km2) and temporal (1 h) resolutions. The interannual variation of monthly N dry deposition is in the range 10-160%, being mostly controlled by the photochemical activity of the atmosphere and the frequency of winds towards the river. The variation of monthly wet deposition values between years is in general greater than a factor of 2. It is mainly affected by the frequency of rainy hours and the precipitation rate during offshore wind conditions, and reaches a factor of 124 as a result of the variation of these variables in a factor of 4 and 3, respectively. These results show that estimated monthly N deposition to coastal waters may vary significantly between years. The evaluation of the atmospheric N that can be transferred to coastal waters can therefore be improved considering several years of atmospheric input data.